On the growth mechanism of electrodeposited PbTe dendrites. Issue 13 (9th March 2016) - Frantz, C.; Zhang, Y.; Michler, J.; Philippe, L.
Abstract : The effect of electrochemical conditions on the morphology of PbTe electrodeposits is studied. The formation of dendrites is found to result from the preferential growth along the <111> directions and first gives rise to cubic nuclei. The growth of these nuclei is found to occur differently under a mixed kinetics-diffusion regime and purely mass transfer limitations. Abstract : This study reports on the electrodeposition of PbTe from nitric acid electrolytes and reveals the effects of electrochemical conditions ( i.e. precursor concentration, overpotential, convection) on the composition and morphology of deposited films. In the absence of convection, near stoichiometric deposits tend to develop dendritic morphologies. Experimental results show that Pb 2+ activity and applied overpotential strongly impact the characteristic dimensions of dendrites. Microstructural analyses highlight highly textured structures in which the stem and branches present the same crystal orientation. The constant angle observed between the different generations of branches is explained by the preferential growth along the [111] direction, i.e. perpendicular to the high surface energy planes. Finally, the nucleation and growth mechanisms of the different types of structures are described on the basis of crystal properties, diffusion conditions, and nucleation rate.